Smart textiles - Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2007)
Smart textiles possess enhanced functionality because of the integration of electronics, chemicals, metals or polymers with regular fibers. This programme gives a brief overview of the development of 'smart textiles' since the 1950s through to the 21st century.
Keywords: Clothing and dress -- Technological innovations; Nanoparticles; Textile fabrics -- Technological innovations